2016
DOI: 10.1073/pnas.1601899113
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of lipids strongly affect the kinetics of the membrane-induced aggregation of α-synuclein

Abstract: Intracellular α-synuclein deposits, known as Lewy bodies, have been linked to a range of neurodegenerative disorders, including Parkinson's disease. α-Synuclein binds to synthetic and biological lipids, and this interaction has been shown to play a crucial role for both α-synuclein's native function, including synaptic plasticity, and the initiation of its aggregation. Here, we describe the interplay between the lipid properties and the lipid binding and aggregation propensity of α-synuclein. In particular, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
379
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 282 publications
(420 citation statements)
references
References 50 publications
35
379
3
3
Order By: Relevance
“…In addition, binding of each of the α-synuclein variants to DMPS vesicles induces a reduction in the melting temperature of the constituent lipids (SI Appendix, Fig. S1C), as previously observed for WT α-synuclein (21), indicating a higher binding affinity of the WT protein and the mutational variants studied here for the membrane in its fluid phase rather than in its gel phase (38).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, binding of each of the α-synuclein variants to DMPS vesicles induces a reduction in the melting temperature of the constituent lipids (SI Appendix, Fig. S1C), as previously observed for WT α-synuclein (21), indicating a higher binding affinity of the WT protein and the mutational variants studied here for the membrane in its fluid phase rather than in its gel phase (38).…”
Section: Resultssupporting
confidence: 81%
“…It is well established, however, that the nucleation process is strongly enhanced in the presence of surfaces, such as those of lipid vesicles (21,35) or hydrophobic polymers [in the form of nanoparticles (36) or macroscopic surfaces (37)]. In the case of lipid membranes, the chemical properties of the lipids composing the membrane were shown to influence very significantly the magnitude by which they can trigger the aggregation of α-synuclein, suggesting a role of the membrane composition in balancing normal and aberrant behavior of the protein (38). In addition, although aggregation is not normally observed under quiescent conditions in the absence of appropriate surfaces, the addition of preformed seed fibrils allows the growth of aggregates Significance Proteinaceous deposits composed primarily of amyloid fibrils of α-synuclein are a hallmark of a range of neurological disorders including Parkinson's disease.…”
mentioning
confidence: 99%
“…Additionally, DLPC membranes are capable of reorganizing the surface and side chain orientation of mature fibrils. Interestingly, a lipid bilayer composed of dilauroyl phosphatidylserine, which shares the acyl chain length and hydrophobic thickness of DLPC, has been shown to promote the aggregation of ␣-synuclein, an amyloid implicated in Parkinson's disease (69). This finding suggests that the inhibition of A␤ aggregation by DLPC may be dependent on peptide, lipid headgroup, or possibly both.…”
Section: Discussionmentioning
confidence: 99%
“…5A), suggesting that the GZ667161-mediated reduction in glycosphingolipids affected the subcellular distribution of α-synuclein. Recent studies have demonstrated that alterations in lipid membrane composition can greatly affect the kinetics of α-synuclein membrane-induced aggregation (31,32).…”
Section: Gz667161 Affects α-Synuclein Proteostasis In a Synucleinopatmentioning
confidence: 99%